Buddhism, Politics, and Nationalism in the Twentieth and Twenty-first Centuries - Borchert, Thomas (Religion compass, 2007)
Buddhism is widely understood as a religion with a global scope. Particularly from the end of the twentieth century, the widespread growth of Buddhism internationally, and the extensive ties between Buddhists institutions, leave the impression of unity within contemporary Buddhism. Nevertheless, in this article, I argue that Buddhism cannot be understood outside of a national context. Although international ties between Buddhists are real and important, Sanghas generally remain under the governance by national governments and monks and nuns remain citizens of particular nation-states. As a result, contemporary Buddhism is marked by a tension between the transnational and the national.